PENGEMBANGAN BAHAN AJAR MENULIS SLOGAN DAN POSTER DENGAN PENDEKATAN PROSES SISWA KELAS VIII SMP SYAICHONA CHOLIL SAMARINDA - Hani Subakti (Kantor Bahasa Kalimantan Timur, 2017)
The research on the developing teaching materials to write slogans and posters with a process approach needed to be studied . This research was conducted based on the mandate of the Indonesian Constitution of Teachers and Lecturers and the findings of the difficulties experienced by teachers and students in the process of learning to write slogans and posters . Therefore, the objectives of the teaching materials development research on slogans and posters writing aimed to (1) know the process of developing teaching materials to write slogans and posters with a process approach; (2) measure the quality of teaching materials writing slogans and posters with a process approach judged from Validity, practicality, and effectiveness .The research methods used in this analysis are research and development analysis (research and development) with Borg and Gall model. This research was conducted in Syaichona Cholil Junior high School, Samarinda . The research and development procedure followed the steps of Borg and Gall which had been tested on the students of grade VIII A and B Syaichona Cholil Junior High School, Samarinda . The research data was obtained through the data of the development process of teaching material of Bahasa Indonesia Book and the quality data of teaching material of Bahasa Indonesia Book . The data analysis technique in this research used descriptive analysis techniques and qualitative analysis techniques.The final resultof Indonesian students’ books using the preferred process approach of Syaichona Cholil Samarinda Junior High School, a validity/good category, the practicality of getting very positive category, and the effectiveness, is categorized as very good and significant category.